2-Acetamidophenol (2-AAP) Suppresses the Progression of Atherosclerosis by Alleviating Hyperlipidemia and Attenuating the Ferroptosis Pathway - Xiaohan Zang; Yongcheng Wang; Cong Han; Lishuang Cui; Haojie Liu; Shuimiao Tian; Kechun Liu; Peihai Li; Chen Sun; Qing Xia; Yun Zhang (Marine Drugs)
Hyperlipidemia and consequent endothelial inflammation, along with foam cell generation, promote the progression of atherosclerosis (AS). Here, we aimed to investigate the effects of 2-acetamidophenol (2-AAP), which was selected by zebrafish phenotypic screening, in alleviating AS by relieving hyperlipidemia and inhibiting foam cell formation, as well as the underlying mechanisms. In a zebrafish hyperlipidemia model, 2-AAP increased lipid-lowering efficacy; alleviated TC, TG, LDL-C, and MDA levels; elevated HDL-C and T-SOD levels; significantly improved intravascular macrophage aggregation; and improved blood flow. In an ox-LDL-induced RAW264.7 model, 2-AAP inhibited lipid phagocytosis in RAW264.7 cells; reduced the intracellular TC, TG, FC, and CE contents; and decreased the CE/TC ratio, thus slowing foam cell generation. In addition, 2-AAP alleviated intracellular ROS and ferrous ion accumulation in RAW264.7 cells, reduced the MDA content, and increased GPX4 viability. Furthermore, transcriptome analyses and gene expression validation showed 2-AAP treatment upregulates genes related to GSH synthesis and transport, such as gclc, gclm, gss, and gpx4a, and enhanced the expression levels of genes involved in the storage and transportation of iron ions, such as fpn1, fth, and g6pd, indicating that 2-AAP dramatically regulated the ferroptosis and glutathione metabolic pathways. Overall, our study demonstrated that 2-AAP demonstrated potential in AS by alleviating hyperlipidemia and attenuating the ferroptosis pathway and provided evidence supporting the future application of 2-AAP in AS treatment.